Analisis Standar Perencanaan Penilaian, Kaidah Penulisan Soal Dan Kriteria Butir Soal Pilihan Ganda Tes Sumatif Fisika Kelas X Pada SMA Kristen 1 Amahai, Kabupaten Maluku Tengah - Uneputty, Venolia Ceylon; Huliselan, Estevanus Kristian; Malawau, Seska (Pattimura University, 2022)
This study aims to analyze the feasibility of summative physics test questions for the even semester of the 2019/2020 school year in class X MIA2 students at SMA Kristen 1 Amahai, Central Maluku Regency, as a learning evaluation tool. The analysis results show that in preparing the questions, educators have been 100% guided by the assessment planning standards set by the BSNP. In addition, the rules for writing multiple-choice questions have been fulfilled 97%. On the other hand, the fulfillment of the criteria for good items from the validity criteria has reached 75% in the very valid and valid categories. Furthermore, the test reliability correlation coefficient is 0.64 in the high category, the difficulty level of the questions with a ratio of 4.5:4:1.5, the discriminatory power in the moderate and good categories was 95%, and the distractor function was 85% in the very good and good categories. Based on the results of the analysis showed that the questions were appropriate to be used as a learning evaluation tool.